Contextualization of Hadical Understanding about Corruption - Rohmansyah Rohmansyah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Corruption is a major issue and become a barrier against advancement of a country including its inhabitants because it is very detrimental to the economy and finances of the State. This paper tried to do the understanding the Hadith are contextually corruption by using descriptive method-analytical. Findings from this research yielded some important things to talk about corruption, namely: first, the forms of corruption among other ghulul (embezzlement), treasonous, risywah, sariqah and gifts. Second, all the scholars of hadith scholars including agreed five forms of corruption are part of their religious offense finally perpetrators punished corruption according to weight and ringannya corruption. Third, the Hadith-Hadith corruption kontektual, understood that corruption does not occur only at the time of the Prophet, but continues to present an extraordinary influence against the injustice in life, aspects of the implementation of the bureaucracy and others. Fourth, aspects of Islamic trends in corruption were forbidden to keep treasures (hifzh al-Mal), both in the aspect of dharuriyah, tahsiniyah and hajiyah her.[Korupsi merupakan masalah besar dan menjadi penghalang terhadap kemajuan suatu negara termasuk penduduknya karena sangat merugikan perekonomian dan keuangan negara. Tulisan ini mencoba melakukan pemahaman hadis korupsi secara kontekstual dengan menggunakan metode deskriptif-analitis. Hasil temuan dari penelitian ini menghasilkan beberapa hal penting yang berbicara tentang korupsi, yaitu: Pertama, bentuk-bentuk korupsi antara lain ghulul (penggelapan), khianat, risywah, sariqah dan hadiah. Kedua, semua para ulama termasuk ulama hadis sepakat lima bentuk korupsi tersebut merupakan bagian dari perbuatan pelanggaran  agama  yang  akhirnya  pelaku  korupsi  mendapatkan  hukuman  sesuai  berat  dan  ringannya korupsi. Ketiga, hadis-hadis korupsi dipahami secara kontektual, bahwa kasus korupsi tidak hanya terjadi pada masa Nabi, namun terus terjadi sampai masa sekarang yang pengaruhnya sangat luar biasa terhadap aspek ketidakadilan dalam kehidupan, pelaksanaan birokrasi dan lain-lain. Keempat, dari aspek maqashid syariah korupsi dilarang untuk memelihara harta (hifzh al-Māl) baik dalam aspek dharuriyah, hajiyah dan tahsiniyah.]